The effect of ergonomic risk factor on musculoskeletal discomfort among delivery workers at courier service industries - Widia, Mirta; Zen, Zayyinul Hayati; Thoyyibah, Shahar; Ezrin Hani, Sukadarin; Nazlin Hanie, Abdullah (AIP Publishing, 2024)
Delivery workers are particularly vulnerable to ergonomic risk factors associated with a musculoskeletal disorder. This is a serious problem that needs to be highlighted because the courier industry continues to grow to maintain that demand continuously. This study aims to investigate the effect of the ergonomic risk factor on musculoskeletal discomfort among delivery workers. About 132 delivery workers from three types of courier industries were involved. Data for this study were collected using five sections of a questionnaire (personal information, general information, personal medical history, occupational history, and work environment information). The association between ergonomic risk factors and musculoskeletal discomfort was tested using the Chi-Square Test. The findings highlighted that there is a significant association between ergonomic risk factors and musculoskeletal discomfort (p<0.05). All body parts were significantly associated with twisted driving posture. Furthermore, shoulder and neck body parts were also significantly associated with weight load and bent forward driving posture.